2018
DOI: 10.2334/josnusd.17-0160
|View full text |Cite
|
Sign up to set email alerts
|

Formation of chemical bonds on zirconia surfaces with acidic functional monomers

Abstract: We investigated the chemical interaction between zirconia surfaces and functional monomers using X-ray photoelectron spectroscopy (XPS). Two types of zirconia disks cleaned with piranha solution were treated with one of two phosphate primers (Alloy Primer, Clearfil Ceramic Primer) or a carboxylic primer (Super-Bond C&B Monomer), and rinsed 3 times with acetone. XPS analysis revealed that phosphorus was incorporated into zirconia when the surface was treated with a primer containing phosphate monomer (10-methac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
(23 reference statements)
2
12
0
1
Order By: Relevance
“…For the non-etchable zirconia surfaces [14], chemical bonding of carboxyl and phosphate functionalized methacrylate monomers with surface Zr, via hydrogen bonding and ionic interaction has been confirmed [31,32], while thiol and silanol functionalized analogues failed to adsorb on zirconia [32]. In the present study, traceable bonds on zirconia were identified only after AB treatment.…”
Section: Discussionsupporting
confidence: 50%
“…For the non-etchable zirconia surfaces [14], chemical bonding of carboxyl and phosphate functionalized methacrylate monomers with surface Zr, via hydrogen bonding and ionic interaction has been confirmed [31,32], while thiol and silanol functionalized analogues failed to adsorb on zirconia [32]. In the present study, traceable bonds on zirconia were identified only after AB treatment.…”
Section: Discussionsupporting
confidence: 50%
“…However, VC delamination from the core structure is frequently observed in the clinical situation [20], and its fracture remains a primary cause of failure [14,27]. Therefore, in achieving acceptable VC bonding in a wide range of clinical applications, alternative treatment methods that ideally utilize chemical adhesion in addition to mechanical retention [38] are required for zirconia ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…It could be due to carboxylic monomers may chemically adhere to zirconia. According to Shimoe et al 30) , in which the bonding between zirconia surfaces and functional monomers was investigated using X-ray photoelectron spectroscopy (XPS) and energy dispersive X-ray microanalysis, an increase in the [C] and [O] intensity peaks was obvious when the zirconia peaks on primed surfaces were masked off by absorbed primer films, denoting that 4-META chemically adheres to the zirconia surface. On the other hand, the difference between 4-META and MDP which 4-META has less adsorption than MDP was elucidated by an analysis of the atomic ratios of [C].…”
Section: Discussionmentioning
confidence: 99%